Hubungan Work Readiness dengan Subjective Well-Being pada Mahasiswa yang Mengikuti Program Magang - Ramadhan, Akrom Daffa; Aulia, Prima (Al-DYAS, 2025)
The high unemployment rate among university graduates reflects a gap between academic competence and work readiness, which in turn affects students’ subjective well-being. This study aims to investigate the relationship between work readiness and subjective well-being among students participating in internship programs. Employing a quantitative approach with a correlational design, the study involved 353 active university students in Indonesia, selected through purposive sampling. Data were collected using researcher-developed questionnaires on work readiness and subjective well-being, and analyzed using Spearman’s rho correlation. The results indicate a strong and significant positive relationship between work readiness and subjective well-being (r = 0.775; p < 0.05), suggesting that higher work readiness is associated with higher levels of subjective well-being. These findings highlight the critical role of internships in strengthening professional competencies while also supporting students’ psychological well-being. The practical implications of this study include recommendations for educational institutions, industry stakeholders, and government bodies to design structured, holistic internship programs oriented toward character development and mental health support. Additionally, the study opens avenues for further exploration into other contributing factors such as social support and the quality of internship programs in enhancing student readiness and well-being.